2018
DOI: 10.1016/j.nicl.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Identical patterns of cortico-efferent tract involvement in primary lateral sclerosis and amyotrophic lateral sclerosis: A tract of interest-based MRI study

Abstract: BackgroundThere is an ongoing debate whether primary lateral sclerosis (PLS) should be regarded as an independent disease entity separate from amyotrophic lateral sclerosis (ALS) or as a slowly progressive variant of ALS.ObjectiveThe study was designed to investigate specific white matter alterations in diffusion tensor imaging (DTI) data from PLS patients by a hypothesis-guided tract-of-interest-based approach compared with ‘classical’ ALS patients and healthy controls, in order to identify microstructural ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…Systematic ex vivo data in patients with a PLS phenotype for the diagnostic proof as definite ALS by the neuropathological demonstration of cerebral TDP43 pathology according to the neuropathological staging concept of ALS ( Braak et al, 2013 ; Braak et al, 2017 ) are lacking yet. In order to assess this neuropathological pattern in MND patients in vivo by magnetic resonance imaging, a group of PLS patients has been subjected to the established hypothesis-guided tract-of-interest (TOI)-based diffusion tensor imaging technique of the brain ( Kassubek et al, 2014 ; Kassubek et al, 2018 ), and the results showed the same microstructural pathological patterns in PLS patients as in ALS, in support of the hypothesis that PLS is a phenotypical variant of ALS ( Müller et al, 2018 ).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Systematic ex vivo data in patients with a PLS phenotype for the diagnostic proof as definite ALS by the neuropathological demonstration of cerebral TDP43 pathology according to the neuropathological staging concept of ALS ( Braak et al, 2013 ; Braak et al, 2017 ) are lacking yet. In order to assess this neuropathological pattern in MND patients in vivo by magnetic resonance imaging, a group of PLS patients has been subjected to the established hypothesis-guided tract-of-interest (TOI)-based diffusion tensor imaging technique of the brain ( Kassubek et al, 2014 ; Kassubek et al, 2018 ), and the results showed the same microstructural pathological patterns in PLS patients as in ALS, in support of the hypothesis that PLS is a phenotypical variant of ALS ( Müller et al, 2018 ).…”
Section: Introductionmentioning
confidence: 79%
“…in neurodegenerative diseases. The application of the TOI technique has previously been applied to show that the PLS brain alteration pattern is like in ALS ( Müller et al, 2018 ). In addition, it has been demonstrated that different DTI protocols can be pooled even in a large multi-centre study ( Müller et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is long recognized that PLS is rarely distinguishable from ALS at the histopathological level and in diffusion-tensor imaging [16]. On the other hand, neuropathological studies in hSP have revealed pallor of the lateral corticospinal tract and, more variably, of the anterior tract within the spinal cord, besides fasciculus gracilis [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the revision of the El Escorial criteria, PLS is described as a restricted phenotype that evolves into ALS in the majority of patients ( Ludolph et al, 2015 ). In vivo , the analysis of WM integrity by regional FA reductions in 50 PLS patients vs. 50 controls showed the alterations along the CST and additionally in frontal and prefrontal brain areas in PLS and ALS patients ( Müller et al, 2018b ). The ALS-staging-related tract-specific analysis demonstrated identical alterations of ALS-related tract systems for PLS and ALS when compared with controls and showed no differences for the comparison between ALS and PLS ( Müller et al, 2018b ).…”
Section: Application Of the In Vivo Staging Approamentioning
confidence: 99%